Relación entre la tasa de urbanización, consumo de energía no renovable y el PIB per cápita para 111 países del mundo: un enfoque de cointegración y causalidad con datos de panel, periodo 1971-2016” - Ortiz Villalta, Cristian Paul (2018)
The notable demands of sustainable energy and the need for the lag and independence of unsustainable energy sources (fossil energy) that in turn affect the production of the primary exporting and oil-dependent countries, in addition to the notable advance and concentration of the population in the urban areas of countries without planning or vocation to produce and develop, pose huge problems for the growth and economic development of countries, therefore, this research has as a general objective "Determine the evolution that exists between the rate of urbanization , non-renewable energy consumption and GDP per capita for 111 countries of the world classified by income groups, by means of an econometric study, period 1971 – 2016”, to examine the short-term, long-term relationship and causality among the variables. data from the World Development Indicators (2017) of the World Bank and Atlas method (2016), we classify countries into four income groups that are: high-income countries, upper-middle-income countries, low-middle-income countries, and low-income countries for purposes of comparison of the panels analyzed. The results show that, through cointegration techniques with panel data, we find evidence that suggests that there is a joint movement between the variables both long and short term; and Granger's causality tests suggest that bidirectional causality exists between the growth rate of GDP per capita and the urbanization rate; at all income levels, except for UMIC and LIC, bidirectional causality was also found between rate of growth of non-renewable energy use and GDP growth rate per capita, in the GLOBAL and HIC and unidirectional in the UMIC and LMIC and no causal direction in the LIC, while unidirectional causality is observed from urbanization to consumption of energy in the GLOBAL, HIC and UMIC panel.